Relationship on operation, human capital management (HCM) and layout of warehouse efficiency in small and medium enterprises (SMEs): The moderating effect of Management Information System (MIS) - Mohd Saifudin, Adam; Abdullah, Haim Hilman; Saud, Mohammad Basir (2010)
Due to the globalize business, the warehouse activities are now becoming the centre of importance to ensure the effective receiving and storage of goods and materials, efficient handling of materials in the manufacturing firms, logistics support in exporting the goods to another destinations as excellent hubs and accurate information of timely delivery and receiving of materials and goods through efficient internet or email networking. This paper focuses on the warehouse efficiencies based on its operations, layout and Human Capital Management (HCM) in SMEs manufacturing firms and its moderating effect with Management Information System (MIS). It discusses the introduction and important of warehouse to in logistics and supply chain activities, the roles of SMEs, the research and objectives questions, a conceptual and theory of framework and methodology of the paper and pilot test of the research. Lastly it would discuss the conclusion and contribution of the research.